Projection of the Precipitation Extremes in Thailand Under Climate Change Scenario RCP8.5 - Amnuaylojaroen, Teerachai (Frontiers in Environmental Science, 2021)
This study explores the predicted extreme precipitation during 2020-2029 over Thailand using the Nested Regional Climate Model (NRCM) output with the RCP8.5 emission scenario. The research used five different extreme precipitation indices, i.e. annual precipitation total (PRCPTOT), annual rainy days number (RD), simple daily intensity index (SDII), consecutive dry days (CDD) and consecutive wet days (CWD). The PRCTOT was generally located in eastern Thailand with significant declining trends, while the increasing trend was found in northern Thailand. The quantity of the PRCPTOT varies marginally from 100 to 200 mm per decade. The annual RD was influenced by negative trends most of Thailand. A remarkable trend is a rising of annual SDII, with major statistical increases ranging from 5% to 20%. A widespread decline in CWD in most regions. The statistically significant pattern of CWD has been geographically concentrated in the northern, southern and eastern regions of Thailand. Southern Thailand continues to decline by (-10) %to (-30) %. A drastic decline has been observed in the south of Thailand. Projected interannual precipitation variability shows that DJF variability is greater than either annual or JJA variability in most years, with the exception of 2022, 2025, and 2026, in which JJA variability is greater than both annual and DJF variability.